Les structures politiques de l’accumulation au prisme de la théorie des champs - Matthieu Ansaloni (Revue de la Régulation)
The geographical redistribution of durum wheat production in France since the early 2000s has led to a redistribution of the possibilities for accumulation of the economic capital derived from it. This article shows that this movement is mainly due to the permanence of the rules that define the characteristics of the commodity ‘durum wheat’. Favouring certain economic forces at the expense of others, these rules weigh on the distribution of the structure of the profits derived from it, and thus on accumulation. This demonstration is an opportunity to show that, interpreted in the light of the school of regulation, Pierre Bourdieu’s economic anthropology can usefully be mobilized to grasp the political structures that organize and sustain accumulation – and to do so in a dynamic way.